2020
DOI: 10.3390/ijms22010143
|View full text |Cite
|
Sign up to set email alerts
|

Does microRNA Perturbation Control the Mechanisms Linking Obesity and Diabetes? Implications for Cardiovascular Risk

Abstract: Metabolic disorders such as obesity and type 2 diabetes (T2D) are considered the major risk factors for the development of cardiovascular diseases (CVD). Although the pathological mechanisms underlying the mutual development of obesity and T2D are difficult to define, a better understanding of the molecular aspects is of utmost importance to identify novel therapeutic targets. Recently, a class of non-coding RNAs, called microRNAs (miRNAs), are emerging as key modulators of metabolic abnormalities. There is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 141 publications
(153 reference statements)
0
13
0
Order By: Relevance
“…Recently, obesity‐induced miRNAs have emerged as key regulators of abnormal glucose and lipid metabolism 13 , 14 . In this study, we first demonstrated a novel glucose and lipid metabolism‐associated miRNA, miR‐4431.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, obesity‐induced miRNAs have emerged as key regulators of abnormal glucose and lipid metabolism 13 , 14 . In this study, we first demonstrated a novel glucose and lipid metabolism‐associated miRNA, miR‐4431.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, dysfunctional adipose tissue can partially account for the alterations of RAAS signaling influencing the surrounding organs, including the vasculature. It is well known the paracrine communication between adipose tissue and skeletal muscle, pancreas and cardiovascular system with the release of adipokines, cytokines and other small molecules, such as extracellular vesicles (EV) deputed to vehicle small RNAs (microRNAs) among others [ 44 ]. For example, miR-27a, which plays a critical for obesity by regulating insulin resistance in adipocytes, seems to facilitate the crosstalk between adipocytes and skeletal muscle, inducing insulin resistance by PPARG [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a very important part of non-coding RNAs (ncRNAs) and are closely associated with key regulators of metabolic abnormalities [ 87 ]. miRNAs are short noncoding RNA sequences of 18 to 25 nucleotides in length that can regulate gene expression and silence [ 88 ].…”
Section: Mirna-mediated Regulationmentioning
confidence: 99%